Taking two to tango: a role for ghrelin receptor heterodimerization in stress and reward - Schellekens, Harriet; Dinan, Timothy G.; Cryan, John F. (Frontiers in Neuroscience, 2013)
The gut hormone, ghrelin, is the only known peripherally derived orexigenic signal. It activates its centrally expressed receptor, the growth hormone secretagogue receptor (GHS-R1a), to stimulate food intake. The ghrelin signalling system has recently been suggested to play a key role at the interface of homeostatic control of appetite and the hedonic aspects of food intake, as a critical role for ghrelin in dopaminergic mesolimbic circuits involved in reward signalling has emerged. Moreover, enhanced plasma ghrelin levels are associated with conditions of physiological stress, which may underline the drive to eat calorie-dense ‘comfort-foods’ and signifies a role for ghrelin in stress-induced food reward behaviours. These complex and diverse functionalities of the ghrelinergic system are not yet fully elucidated and likely involve crosstalk with additional signalling systems. Interestingly, accumulating data over the last few years has shown the GHS-R1a receptor to dimerize with several additional G-protein coupled receptors (GPCRs) involved in appetite signalling and reward, including the GHS-R1b receptor, the melanocortin 3 receptor (MC3), dopamine receptors (D1 and D2), and more recently, the serotonin 2C receptor (5-HT2C). GHS-R1a dimerization was shown to affect downstream signalling and receptor trafficking suggesting a potential novel mechanism for fine-tuning GHS-R1a receptor mediated activity. This review summarizes ghrelin’s role in food reward and stress and outlines the GHS-R1a dimer pairs identified to date. In addition, the downstream signalling and potential functional consequences of dimerization of the GHS-R1a receptor in appetite and stress-induced food reward behaviour are discussed. The existence of multiple GHS-R1a heterodimers has important consequences for future pharmacotherapies as it significantly increases the pharmacological diversity of the GHS-R1a receptor and has the potential to enhance specificity of novel ghrelin-targeted drugs.